Radiation Induced Xerostomia: Current Concepts and Future Trends - Krishnan, Manu; Iyer, Satish R; Chakraborti, Kanti Lal; Seema, Saraswathy; Sekhri, Tarun (Defence Life Science Journal, 2017)
Radiation induced xerostomia is a persistent clinical presentation that affects the quality of life in head and neck cancer patients even with the best of the intensity modulated radiotherapy protocols. Comprehensive review of the anatomic, histologic, developmental and neuronal entities of salivary glands from a regenerative perspective, ensuing radiation is taken. It also evaluates the systemic and glandular radiation responses that form the early and late clinical changes. From these, the article submits probable strategies; based on the current knowledge and future challenges involved, in reversing radiation induced xerostomia. Further, it elaborates on the status of radioprotectors and mitigators including the recently reported biologic and chemical derivatives and proposes the rationale of using combination radioprotector therapy in radiation injuries. A brief of palliative regimes, alternate treatment modes and technologic advancements in radiotherapy are also explained. Salivary gland histologic components, which need to be protected in the emerging radiotherapy protocols and can be targeted in different salivary gland regeneration therapies is highlighted. The paper contributes to an improved understanding in radiation induced xerostomia and deliberates on novel mechanisms towards enhancing quality of life in head and neck cancer radiotherapy patients.